2020
DOI: 10.1007/s12029-020-00468-y
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Ratio Is an Independent Prognostic Factor for Patients with Siewert Type II Adenocarcinoma of Esophagogastric Junction: Results from a 10-Year Follow-up Study

Abstract: Background Emerging evidences suggest that lymph node ratio (LNR), the number of metastatic lymph node (LN) to the total number of dissected lymph nodes (NDLN), may predict survival in multiple types of solid tumor. However, the prognostic role of LNR in adenocarcinoma of the esophagogastric junction (AEG) remains uninvestigated. The study is intended to determine the prognostic value of LNR in the patients with Siewert type II AEG. Methods A total of 342 patients with Siewert type II AEG who underwent R0 rese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…( 6 ) showed that the number of resected lymph nodes ≥12 was an independent predictor of survival for Siewert type II AEG. Some retrospective studies on AEG demonstrated a high prognostic relevance of the lymph node ratio (LNR) but not of the absolute number of lymph nodes ( 7 , 8 ). Another study on Western populations showed no significant difference in survival between the extended and the less extended lymphadenectomy ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…( 6 ) showed that the number of resected lymph nodes ≥12 was an independent predictor of survival for Siewert type II AEG. Some retrospective studies on AEG demonstrated a high prognostic relevance of the lymph node ratio (LNR) but not of the absolute number of lymph nodes ( 7 , 8 ). Another study on Western populations showed no significant difference in survival between the extended and the less extended lymphadenectomy ( 9 ).…”
Section: Introductionmentioning
confidence: 99%